The effects of ski type on accelerations and forces during alpine skiing - Seifert, J. G.; Scheiber, P.; Kipp, R. W.; Müller, E. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
The alpine ski industry is experiencing a shift towards wider recreational skis. There can be upwards of an additional 3cm width from the binding plate to the ski edge with a wide ski. Yet, little is known how this additional width affects acceleration and force patterns during skiing. The purpose of this study was to compare boot forces and accelerations between a narrow width ski (GS ski) and a wide width ski (powder ski). Methods: Data collection began following approval from the IRB. Following a warmup run with each ski, 8 collegiate skiers (FIS GS pts: 71 (29) ) completed 1 run with a 65 mm mid-length width ski (GS; FIS GS) and 1 run with a 102 mm mid-length width ski (WIDE; K2 Coomback). The standardized run consisted of 10 gates that were set 20.5m downhill and 6m offset. The run was groomed nightly prior to data collection. Data from each of the 6 middle turns were averaged and used in analyses. Unidirectional force was measured with force insoles (100 Hz sampling frequency) and boot accelerations were measured with 3-D accelerometers (50 Hz sampling frequency). Data are listed as mean (+/-SD). Alpha level of significance was p < 0.05. Results: No difference in completion time for the 6 measurement gates was observed between WIDE (8.20 (1.39) sec) and GS (8.16 (1.16) sec) skis. The relative total force (L + R legs) and relative force on the inner foot were greater for GS (1.32 (.24) N/kg BW; 0.41 (.11) N/kg BW) than WIDE (1.23 (.20) N/kg BW; 0.34 (.13) N/kg BW). No difference between skis was found for relative force for the outer foot. Co-loading for the inner foot was greater in GS (31.1 (7.8) %) than WIDE (26.7 (7.1) %). No differences between skis were observed for average acceleration in any of the 3 axes. The range in acceleration for the x and y axes were greater for WIDE (x: 64.7 (6.9); y: 66.6(12.7) m/s^2) compared to GS skis (x: 55.9 (9.8); y: 54.9 (6.9) m/s2). Discussion: Significant differences in forces and accelerations were found between the WIDE and GS skis. The greater load on the inner leg for the GS skis indicates an increased "two-legged skiing style", due to the self-steering mechanism of these skis. The greater range in accelerations was seen by significantly increased accelerations in the vertical and sagittal planes for WIDE. The significant differences between skis for the ranges and accelerations, within a turn, could indicate less stability for the skier using the WIDE ski on a groomed run. It may be assumed that for each change in acceleration, the body responds with some form of muscular contraction. Further research should evaluate i) force and acceleration data in a deep snow environment and ii) the physiologic effects using wider profile skis during on-piste and off-piste runs.